Rapid onset honeycombing fibrosis in spontaneously breathing patient with COVID-19. Issue 2 (27th August 2020) - Combet, Margot; Pavot, Arthur; Savale, Laurent; Humbert, Marc; Monnet, Xavier
A 38-year-old man presented with a 6-day history of gradually worsening cough and asthenia and secondary anosmia and agueusia. He had no prior personal medical history. His mother had a history of diabetes mellitus and his son was followed for haemophilia A. His spouse had exhibited similar symptoms a week earlier. Patients with COVID-19 should be monitored for rapid onset honeycombing fibrosis https://bit.ly/2B7fRcA